Editorial introduction: geography and collective memories through art. Issue 1 (2nd January 2023) - Castro, Laura Rodriguez; Barry, Kaya; Bhattacharya, Diti; Pini, Barbara; Boyd, Candice; Ben, Dorell; Bayes, Chantelle; Berger, Becky Nevin; Narayan, Pallavi; Lobo, Michele; Ginsberg, Nina; Hine, Amelia
ABSTRACT: ' Art' and 'memory' are prominent areas of inquiry in geographical research. Artistic and memory work often overlap in our studies through practices and processes aimed at bringing people together in experimental, affective, and collective ways. In this introduction to the special issue, we write collectively as 12 authors to reflect on the histories, inspirations, and future trajectories of these intersecting concerns in geographical research. Our reflections stem from our collective participation and discussions of issues at the intersections of art, memory and geographical research, during an online workshop and our individual-and-collective reflections later through the process of writing this piece. We hope our discussions further interest on the possibilities for creative, collaborative, and decolonial interventions to memory in geography. And, incidentally, we hope that our editorial may be of interest for future research into the value and practices of collective geographic scholarship.